2009
DOI: 10.1007/s11127-009-9443-x
|View full text |Cite
|
Sign up to set email alerts
|

Bread and the attrition of power: Economic events and German election results

Abstract: Bread and Peace model, Elections, Vote share, Real per capita disposable income growth, E6, H11, P16,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The relationship is remarkably similar in many other countries. In Germany, for example, a recent study of post-WWII election results shows that a 1% change in income produces a 2% change in party vote in national elections (Bartool & Sleg, 2009). A 2006 article on Turkish elections between 1950 and 2004 shows similar results (Akarca & Tamsel, 2006).…”
Section: Introduction and Theorymentioning
confidence: 96%
“…The relationship is remarkably similar in many other countries. In Germany, for example, a recent study of post-WWII election results shows that a 1% change in income produces a 2% change in party vote in national elections (Bartool & Sleg, 2009). A 2006 article on Turkish elections between 1950 and 2004 shows similar results (Akarca & Tamsel, 2006).…”
Section: Introduction and Theorymentioning
confidence: 96%
“…(2011) suggest that government expenditure is positively associated with the deficit, aligning with the findings of (Anwar & Ahmad, 2012). Moreover, Batool and Sieg (2009) investigated the political impacts of the budget deficits and modelled elections and quality of democracy to explore the relationship between the political factors and Budeget Deficit.They concluded that the quality of democracy has positive and significant impact on reducing the budget deficit where., the effects of elections in the long run are insignificant. Similar findings of the relationship of budget deficit and the role of corruption and weak institutions were unveiled by the Ullah and Baber (2014).…”
Section: Introductionmentioning
confidence: 99%
“…The author also recommended a policy that suggests that consolidated public sector deficit should be used in research instead of national government fiscal balance as a dependent variable while the tax management system should be improved strictly. Batool and Sieg (2009) estimated the behavior of budget deficit with election using the annual dataset from 1973 to 2009. They found election year increases the budget deficit due to net government budgetary borrowings and borrowing from the banking sector.…”
mentioning
confidence: 99%
“…With respect to Germany, the literature on VP functions has majorily taken place at the macro level (Frey and Garbers (1972), Kirchgässner (1974), Kirchgässner (1985Kirchgässner ( , 1986, Kirchgäss-ner (1991), Feld and Kirchgässner (2000), Batool and Sieg (2009)). Most authors find a significant effect of economic conditions on government popularity, but the relationship sometimes gets "lost" (Kirchgässner, 2009).…”
Section: Introductionmentioning
confidence: 99%